The Effect of Fiber Length Variations on the Composite Fiber of Oil Palm Empty Bunches (OPEB) on Tensile Strength - Reksi Dwi Cahyanto; Agus Mujianto; Binyamin Binyamin; Andi Nugroho (Universitas Muhammadiyah Sidoarjo, 2022)
Composite is a combination of materials formed from mixing between two or more of the forming materials. This research aims to determine the effect of variations in fiber length with lengths of 4cm, 6cm, and 8cm with a volume fraction of OPEFB fiber of 30% and NaOH alkaline immersion for 2 hours. The tests carried out were tensile testing using ASTM D3039 and bending testing using ASTM D7264. Based on the study's results with the 30% OPEFB fraction with the highest tensile strength yield, the 8cm fiber length of 13,33 MPa was achieved. Meanwhile, the lowest value was achieved with a length of 4cm of 3,2MPa.